Building a successful minimally invasive mitral valve repair program before introducing the robotic approach: The Massachusetts General Hospital experience - van Kampen, Antonia; Goudot, Guillaume; Butte, Sophie; Paneitz, Dane C.; Borger, Michael A.; Badhwar, Vinay; Sundt, Thoralf M.; Langer, Nathaniel B.; Melnitchouk, Serguei (Frontiers in Cardiovascular Medicine, 2023)
Background: Patients with mitral valve prolapse (MVP) requiring surgical repair (MVr) are increasingly operated using minimally invasive strategies. Skill acquisition may be facilitated by a dedicated MVr program. We present here our institutional experience in establishing minimally invasive MVr (starting in 2014), laying the foundation to introduce robotic MVr. Methods: We reviewed all patients that had undergone MVr for MVP via sternotomy or mini-thoracotomy between January 2013 and December 2020 at our institution. In addition, all cases of robotic MVr between January 2021 and August 2022 were analyzed. Case complexity, repair techniques, and outcomes are presented for the conventional sternotomy, right mini-thoracotomy and robotic approaches. A subgroup analysis comparing only isolated MVr cases via sternotomy vs. right mini-thoracotomy was conducted using propensity score matching. Results: Between 2013 and 2020, 799 patients were operated for native MVP at our institution, of which 761 (95.2%) received planned MVr (263[34.6%] via mini-thoracotomy) and 38 (4.8%) received planned MV replacement. With increasing proportions of minimally invasive procedures (2014: 14.8%, 2020: 46.5%), we observed a continuous growth in overall institutional volume of MVP (n=69 in 2013; n=127 in 2020) and markedly improved institutional rates of successful MVr, with 95.4% in 2013 vs. 99.2% in 2020. Over this period, a higher complexity of cases were treated minimally-invasively and increased use of neochord implantation ± limited leaflet resection was observed. Patients operated minimally invasively had longer aortic cross-clamp times (94 vs. 88min, p=0.001) but shorter ventilation times (4.4 vs. 4.8hours, p=0.002) and hospital stays (5 vs. 6 days, p<0.001) than those operated via sternotomy, with no significant differences in other outcome variables. A total of 16 patients underwent robotically assisted MVr with successful repair in all cases. Conclusion: A focused approach towards minimally invasive MVr has transformed the overall MVr strategy (incision; repair techniques) at our institution, leading to a growth in MVr volume and improved repair rates without significant complications. On this foundation, robotic MVr was first introduced at our institution in 2021 with excellent outcomes. This emphasizes the importance of building a competent team to perform these challenging operations, especially during the initial learning curve.